Orientasi Tafsir Sains: Analisis Ayat-Ayat tentang Air dalam al-Qur’an - M. Sultan Amirudin; Hidayatullah Ismail; Afrizal Nur (Universitas Darussalam Gontor, 2023)
Allah has created everything by His power, One of His greatness is the creation of water which is needed by living things on this earth. Water is a very important element for the life of living things. Like plants need water to grow. There are many verses that talk about water in the Quran. In Arabic, water is called the word “al-maa”. This research was conducted to find out the meaning and nature of water in the Qur'an from a scientific perspective and the methods of the mufassirs in interpreting the Kauniyyah verses. This research is library research using the thematic interpretation method (thematic), namely collecting verses of the Qur’an related to water, conducting an analysis with the interpretation of tahlili, and then drawing conclusions. The results obtained in this study are water in Arabic is called the word “al-maa’” it turns out that water is mentioned in the Qur'an 63 times in 41 surahs, and has different kinds according to the type and benefits. The method used by the mufassir to interpret the Kauniyyah verses is to pay attention to linguistic rules, verse correlation, established scientific facts, and use a thematic approach.